Spectroscopic properties of poly(9,9-dioctylfluorene) thin films possessing varied fractions of -phase chain segments: enhanced photoluminescence efficiency via conformation structuring - Perevedentsev,A; Chander,N; Kim,J-S; Bradley,DDC (Journal of Polymer Science Part B-Polymer Physics, 2016)
Poly(9,9-dioctylfluorene) (PFO) is a widely studied blue-emitting conjugated polymer, the optoelectronic properties of which are strongly affected by the presence of a well-defined chain-extended “β-phase” conformational isomer. In this study, optical and Raman spectroscopy are used to systematically investigate the properties of PFO thin films featuring a varied fraction of β-phase chain segments. Results show that the photoluminescence quantum efficiency (PLQE) of PFO films is highly sensitive to both the β-phase fraction and the method by which it was induced. Notably, a PLQE of ∼69% is measured for PFO films possessing a ∼6% β-phase fraction induced by immersion in solvent/nonsolvent mixtures; this value is substantially higher than the average PLQE of ∼55% recorded for other β-phase films. Furthermore, a linear relationship is observed between the intensity ratios of selected Raman peaks and the β-phase fraction determined by commonly used absorption calibrations, suggesting that Raman spectroscopy can be used as an alternative means to quantify the β-phase fraction. As a specific example, spatial Raman mapping is used to image a mm-scale β-phase stripe patterned in a glassy PFO film, with the extracted β-phase fraction showing excellent agreement with the results of optical spectroscopy.